Impact of Long Non-coding RNAs Associated With Microenvironment on Survival for Bladder Cancer Patients - Lin, Gaoteng; Guo, Baoyin; Wei, Yulei; Lan, Tianjie; Wen, Simeng; Li, Gang (Frontiers in Genetics, 2020)
Background: Cumulative evidence from several tumor studies, including bladder cancer, emphasizes the importance of tumor microenvironment (TME) in tumorigenesis, development, and metastasis which can be regulated by long noncoding RNAs (lncRNAs). This study aims to identify bladder cancer (BC) microenvironment associated lncRNAs for their prognostic value predicting the survival of BC patients. Methods: The data of BC patients regarding the lncRNAs expression and corresponding clinical characteristics were obtained from The Cancer Genome Atlas (TCGA). The Cox regression analysis and the least absolute shrinkage and selection operator (LASSO) regression analysis were performed to screen lncRNAs following the calculation of the immune score for each sample. For the screened lncRNAs, a risk score model was constructed to predict the survival, and 3-year and 5-year overall survival (OS) rates were assessed using a nomogram. The calibration curve and concordance index (C-index) validated the performance of the nomogram. Finally, to explore the potential function related to the screened lncRNAs, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis were performed. Results: The multivariate Cox regression analysis screened five TME associated lncRNAs regarded as independent factors influencing the tumor progression. The corresponding risk score model was established as follows: (-0.15816 AC064805.1) + (0.10015 AC084033.3) + (-0.17977 AC092112.1) + (-0.05673AC103691.1) + (0.17789 AL391704.1) + (-0.16258 LINC00892). The C-index for the nomogram was 0.63 (95% CI: 0.625-0.635). Also, the calibration curve verified the predictive effectiveness by showing a good concordance between the nomogram prediction and the actual observation. GO and KEGG analysis demonstrated that six TME associated lncRNAs were most likely linked to tumor metastasis and progression. Conclusion: The present study determined six lncRNAs as independent immuno-biomarkers in the TME, constructed a nomogram to predict their prognostic value, and investigated the potential biological processes to understand their regulatory roles in the progression of BC.